Rethinking disability a disability studies approach to inclusive practices - Valle, Jan W. 1956-; Connor, David J. 1961- (Routledge, Taylor & Francis Group, 2019)
Now on its second edition, Rethinking Disability introduces new and experienced teachers to ethical framings of disability and strategies for effectively teaching and including students with disabilities in the general education classroom. Grounded in a disability studies framework, this text's unique narrative style encourages readers to examine their beliefs about disability and the influence of historical and cultural meanings of disability upon their work as teachers. The second edition offers clear and applicable suggestions for creating dynamic and inclusive classroom cultures, getting to know students, selecting appropriate instructional assessment strategies, co-teaching, and promoting an inclusive school culture. this second edition is fully revised and updated to include a brief history of disability through the ages, the relevance of current educational policies to inclusion, technology in the inclusive classroom, intersectionality and its influence upon inclusive practices, working with families, and issues of transition from school to the post-school world. Each chapter now also includes a featured "voice from the field" written by persons with disabilities, parents, and teachers